2007
DOI: 10.1080/00103620701277783
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Effect of Lime, Phosphorus, and Iron Amendments on Water‐Extractable Lead and Arsenic in Orchard Soils

Abstract: Lead arsenate was extensively used to control insects in apple and plum orchards in the 1900s. Continuous use of lead arsenate resulted in elevated soil levels of lead (Pb) and arsenic (As). There are concerns that As and Pb will become solubilized upon a change in land use. In situ chemical stabilization practices, such as the use of phosphate-phosphorus (P), have been investigated as a possible method for reducing the solubility, mobility, and potential toxicity of Pb and As in these soils. The objective of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
2
11
1
1
Order By: Relevance
“…An alternative explanation regarding the relationships between the soil pH, DOC and enzyme activities involved the masking effect from higher concentrations of As WS fractions in both mine tailings (Bhattacharyya et al 2008). In fact, concentrations of As WS fractions in the present study were higher than those observed in previous studies using As-contaminated agricultural soils (Bhattacharyya et al 2008), As-contaminated landfill site soils (Hartley et al 2004) and As-contaminated orchard soils (Codling and Dao 2007). It was concluded from these statistical analyses that the equation with As WS fraction gave the best prediction of the soil enzyme activities in both mine tailings samples.…”
Section: As Fractionationcontrasting
confidence: 82%
See 2 more Smart Citations
“…An alternative explanation regarding the relationships between the soil pH, DOC and enzyme activities involved the masking effect from higher concentrations of As WS fractions in both mine tailings (Bhattacharyya et al 2008). In fact, concentrations of As WS fractions in the present study were higher than those observed in previous studies using As-contaminated agricultural soils (Bhattacharyya et al 2008), As-contaminated landfill site soils (Hartley et al 2004) and As-contaminated orchard soils (Codling and Dao 2007). It was concluded from these statistical analyses that the equation with As WS fraction gave the best prediction of the soil enzyme activities in both mine tailings samples.…”
Section: As Fractionationcontrasting
confidence: 82%
“…In the present study, treatments with ZVI largely reduced both the As WS and As NSS fractions. Generally, Fe oxide has a high affinity for the adsorption of As; therefore, the mobility of As in soils is markedly associated with the presence of Fe oxide on the soil surface (Codling and Dao 2007). Of the many Fe sources, Fe(II) with SO 4 and ZVI are well known and commonly used as stabilizing agents for As (Koo et al 2011b;Kumpiene et al 2008).…”
Section: As Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic As can be relatively mobile in soils in both oxidation states [55,56], particularly in alkaline soils. Arsenic may form insoluble compounds with Fe and Al oxides [56,57], be adsorbed to organic matter or hydroxyl groups on clay minerals [58], and be desorbed from these sites by phosphate fertilizers [57]. However, Huang and Matzner [55] argued that sorption by organic matter was of minor importance in most soils.…”
Section: Arsenicmentioning
confidence: 99%
“…As formas oxianiônicas de arsênio nos solos ricos em óxidos de ferro, estão envolvidas na adsorção específica desse elemento (Waychunas et al, 1993;Bhattacharya et al, 2007) e competem com os fosfatos (Wasay et al, 2000). A remoção do arsênio por dessorção com soluções de fosfato tem sido usada para lavagem deste elemento em solos contaminados (Codling & Dao, 2007). Nesta técnica, é necessário que, posteriormente, se trate o efluente gerado sendo que a remoção do arsênio de efluentes contaminados tem sido realizada por coagulação, sedimentação e filtração (Nguyen et al, 2006).…”
Section: Introductionunclassified